Uneasy encounters: Youth, social (dis)comfort and the autistic self. (July 2017) - Coleman-Fountain, Edmund
Abstract: Notions of deficit and 'faultiness' shape depictions of the association between autism and uneasy social relationships. That framing has been the focus of critique by autistic activists and scholars who, exploring autistic people's sociality, reframe issues of social difficulty in terms of inequality and discomfort. Located within this set of debates, the article analyses data from a UK based study of mental health narratives derived from semi-structured interviews with 19 autistic young adults aged 23 to 24. The NIHR funded the study, and a UK National Health Service Research Ethics Committee gave ethical approval. Sociality and social difficulties, feelings of discomfort, and perceptions of the autistic self as 'faulty' were themes of the study. Exploring the nexus of inequality, non-autistic social power, fears about social performance and (dis)comfort that underpinned the accounts, the article explores the conclusions the young adults reached about social difficulty. Critically examining notions of improvability, the article contributes to debates about sociality, social difficulty and comfort by questioning the assumption that social dysfunction is due to autistic 'fault'. The article concludes with a discussion of inequality in autistic and non-autistic encounters, and of the social dynamics that deny autistic people social comfort. Highlights: Sociality is a significant concern for autistic young adults. That sociality can be a source of comfort but also a source of discomfort. Non-autistic others' negative judgements can produce a sense of individual failure. Improving social skills is a focus of autistic young adults everyday activities. Anxiety can be related to the effort to improve socially.